Math, asked by kaurharjot2807, 3 months ago

(5+square root 5)(5-squaure root 5)

Answers

Answered by Anonymous
0

Answer:

= (5+√5)(5-√5)

= (a+b)(a-b)=a²-b²

Here, a=5 & b=√5

= (5)²-(√5)²

= 25-5

= 20

_______________.

Answered by lalnunkimahmarjoute
0

(5 +  \sqrt{5} )(5 -  \sqrt{5} )

the term is given as (a + b)(a - b)

(a + b)(a - b) =  {a}^{2}  -  {b}^{2}

∴(5 +  \sqrt{5} )(5 -  \sqrt{5} ) =  {(5)}^{2}  -  { (\sqrt{5}) }^{2}

 \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \:  \:  \:  \: = 25 - 5

\:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  \:  \: \:  \:  \:  = 20

Similar questions